Aortic Stenosis Recent Advances, New Perspectives and Applications - Aronow, Wilbert S. (IntechOpen, 2022)
Aortic stenosis is one of the most common and serious valvular diseases in the elderly. Its prevalence increases with age and treatment is always surgical. This book provides a comprehensive overview of aortic stenosis diagnosis and treatment. Chapters address such topics as the use of computer tomography in assessing aortic stenosis, role of frozen allografts in aortic valve surgery, transcatheter aortic valve implantation (TAVI), the Ross procedure, and more.